Incidence of hip fracture in underweight individuals: a nationwide population‐based cohort study in Korea. Issue 5 (19th July 2022) - Han, Sangsoo; Park, Jiwon; Jang, Hae‐Dong; Nah, Sangun; Boo, Joonhyeok; Han, Kyungdo; Hong, Jae‐Young
Abstract: Background: Hip fracture is a major public health problem worldwide and being underweight is a risk factor for fractures. Few studies have investigated the association between being underweight and hip fracture in the general population. The present study investigated the incidence of hip fracture in a large population cohort based on detailed information about the degree of underweight. Methods: A nationwide retrospective cohort study of adults ≥40 years of age included 962, 533 subjects who were not overweight or obese in 2009. The incidence and risk of hip fracture occurring between 2010 and 2018 was assessed based on the degree of underweight. Based on body mass index (BMI), the study population was categorized into normal (18.50–22.99 kg/m 2 ), mild (17.00–18.49 kg/m 2 ), moderate (16.00–16.99 kg/m 2 ), and severe underweight (<16.00 kg/m 2 ) groups. Cox proportional hazards analyses were performed to calculate the hazard ratio (HR) for the hip fracture based on the degree of underweight in reference to the normal weight. Results: Compared with subjects who were normal weight, those who were classified as mild underweight (1.03/1000 person‐years (PY) increase in incidence rate (IR); adjusted HR (aHR) 1.61; 95% confidence interval (CI) 1.48–1.76), moderate underweight (2.04/1000 PY increase in IR; aHR 1.85; 95% CI 1.65–2.08), or severe underweight (4.58/1000 PY increase in IR; aHR 2.33; 95% CI 2.03–2.66) were at significantly increased risk of hip fracture. Conclusions: The severity of underweight was significantly associated with risk of hip fracture. The subdivision of underweight helps to estimate fracture risk more accurately.